Method of Inverse Operator for the Recover Input Signal - Ivanyuk, V.A. (Математичне та комп'ютерне моделювання. Серія: Технічні науки, 2018)
There have been considered the methods of construction of the inverse operator for the restoration of signals in conditions of weak nonlinear dynamic and nonlinear static distortions in the registration devices and transmission of continuous signals are considered. The simplest structure of the implementation block of the inverse operator is based on the adder, whose second inverse communication competitor includes the simulation model of the direct operator. A linear inertia-free unit with a set transmission factor is used as regularizer. Розглянуто методи побудови оберненого оператора для відновлення сигналів при умовах слабких нелінійних динамічних і нелінійних статичних спотворень у пристроях реєстрації та передачі неперервних сигналів. Найпростіша структура блока реалізації оберненого оператора будується на основі накопичуваного суматора, у другий контур оберненого зв’язку якого включена імітаційна модель прямого оператора. В якості регуляризатора використано лінійний безінерційний блок із визначеним коефіцієнтом передачі.